Crystal structures of two nickel(II) macrocyclic salts: (5,7,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane)nickel(II) bis(perchlorate) monohydrate and (5,7,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane)nickel(II) dibromide trihydrate - Corfield, Peter W. R. (Acta Crystallogr E Crystallogr Commun, 2019)
The crystal structure of the Ni-14 macrocycle salt, (5,7,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane)nickel(II) bis(perchlorate) hemihydrate, [Ni(C(16)H(36)N(4))](2)(ClO(4))(4)·H(2)O, contains two different diasteriomeric macrocyclic cations in the asymmetric unit, one with two NH protons on each side of the cation (Ia), and the other with all four NH protons on the same side (Ib). The crystal structure of the bromide trihydrate salt of the same Ni-14 macrocyclic cation, namely (5,7,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane)nickel(II) dibromide trihydrate, [Ni(C(16)H(36)N(4))]Br(2)·3H(2)O (II), contains only the same diastereomer as Ib, with the four N—H bonds on the same side. The geometry around the Ni atom differs slightly between the two diastereomeric cations, as the mean Ni—N distance in Ia is 1.952 (2) Å, while that for Ib and II is 1.928 (2) Å. The hexamethyl substitution in all three macrocyclic cations has the two dimethyl-substituted C atoms cis to one another, different from the trans 5,5,7,12,12,14-hexamethyl Ni-14 cations found in all but one of the many published crystal structures of hexamethyl Ni-14 macrocycles. In each of the two crystal structures, the anions, water molecules, and N—H protons of the macrocyclic cations form extensive hydrogen-bonded zigzag chains propagating along [001] in I and [010] in II.